Patient selection for long-term secondary prevention with ticagrelor: insights from PEGASUS-TIMI 54. (11th November 2022) - Bonaca, Marc P; Im, KyungAh; Magnani, Giulia; Bansilal, Sameer; Dellborg, Mikael; Storey, Robert F; Bhatt, Deepak L; Steg, P Gabriel; Cohen, Marc; Johanson, Per; Braunwald, Eugene; Sabatine, Marc S
Abstract: Aim: In patients with prior myocardial infarction (MI) on aspirin, the addition of ticagrelor reduces ischaemic risk but increases bleeding risk. The simultaneous assessment of baseline ischaemic and bleeding risk may assist clinicians in selecting patients who are most likely to have a favourable risk/benefit profile with long-term ticagrelor. Methods and results: PEGASUS-TIMI 54 randomized 21 162 prior MI patients, 13 956 of which to the approved 60 mg dose or placebo and who had all necessary data. The primary efficacy endpoint was cardiovascular death, MI, or stroke, and the primary safety outcome was TIMI major bleeding; differences in Kaplan–Meier event rates at 3 years are presented. Post-hoc subgroups based on predictors of bleeding and ischaemic risk were merged into a selection algorithm. Patients were divided into four groups: those with a bleeding predictor ( n = 2721, 19%) and then those without a bleeding predictor and either 0–1 ischaemic risk factor (IRF; n = 3004, 22%), 2 IRF ( n = 4903, 35%), or ≥3 IRF ( n = 3328, 24%). In patients at high bleeding risk, ticagrelor increased bleeding [absolute risk difference (ARD) +2.3%, 95% confidence interval (CI) 0.6, 3.9] and did not reduce the primary efficacy endpoint (ARD +0.08%, 95% CI −2.4 to 2.5). In patients at low bleeding risk, the ARDs in the primary efficacy endpoint with ticagrelor were −0.5% (−2.2, 1.3), −1.5% (−3.1, 0.02), and −2.6% (−5.0, −0.24, P = 0.03) in those with ≤1, 2, and 3 risk factors, respectively ( P = 0.076 for trend across groups). There were significant trends for greater absolute risk reductions for cardiovascular death ( P -trend 0.018), all-cause mortality ( P -trend 0.027), and net outcomes ( P -trend 0.037) with ticagrelor across these risk groups. Conclusion: In a post-hoc exploratory analysis of patients with prior MI, long-term ticagrelor therapy appears to be best suited for those with prior MI with multiple IRFs at low bleeding risk. Clinical Trial Registration: NCT01225562 ClinicalTrials.gov Structured Graphical Abstract: Structured Graphical Abstract Characteristics (left) and distribution of patients (middle) in PEGASUS-TIMI 54 by categories of high bleeding risk, low bleeding risk with 0–1 ischaemic risk factors, low bleeding risk with 2 ischaemic risk factors, and low bleeding risk with ≥ 3 ischaemic risk factors and the absolute risk difference for the composite of cardiovascular death, myocardial infarction or stroke with ticagrelor vs. placebo over 3 years for each group (right). CAD, coronary artery disease; CV, cardiovascular; MI, myocardial infarction.